A Proposed Knowledge Management System to Improve the Business Growth At PT. Multi Guna Equipment - Dian Angelina; Dedy Sushandoyo (UniSadhuGuna Business School, 2023)
The construction equipment industry in Indonesia, in which the lifting equipment is a part of, is showing promising growth with an estimated value of 4.5 billion US dollars in 2028, growing at a compound annual growth rate (CAGR) of 6.79% during the period of 2021-2028. PT. Multi Guna Equipment (PT. MGE) is one of the authorized distributors of lifting equipment specializing in reach stackers and harbour mobile cranes from Konecranes – a company based in Finland. In recent years, PT. MGE has experienced stagnant business growth, despite the enormous potential demand for lifting equipment in Indonesia due to the numerous construction projects that are a priority for the Government. The obstacles that contribute to the stagnant business growth of PT. MGE are related to the absence of a system to manage knowledge in the company. In light of these circumstances, the company needs a structured and effective system for managing knowledge, which is through the implementation of a Knowledge Management (KM) system. In doing this, the research is based on two research questions. The first is how can a knowledge management system be proposed to improve the business growth of PT. MGE, and the second is what is the implementation plan for the proposed knowledge management system. These two research questions will be answered using theories related to knowledge, knowledge management, and two knowledge management frameworks, namely People, Process, Technology (PPT) and Socialization, Externalization, Combination, Internalization (SECI). Because a qualitative method is used in this research, data is collected through interviews and observations, which are then analyzed using thematic analysis. The results of data collection show that there are several issues related to the PPT and SECI frameworks. These issues range from the limited sales knowledge and sales skills possessed by salespeople, the lack of knowledge sharing processes within and between teams, the lack of proper knowledge transfer, difficulty in accessing knowledge and information due to manual access, and others. Through the utilization of PPT and SECI frameworks, the author was able to design a knowledge management system by formulating several tools, for example, Coaching, Training, Knowledge café, Lesson-learned documents, K-based exit interview, repository, and e-learning. With a total of 13 (thirteen) knowledge management tools or techniques, the company now has the ability to identify the knowledge needed, capture the knowledge, store the knowledge, share the knowledge, and effectively utilize knowledge and information which can improve the organization’s performance, enhance decision-making processes, and foster innovation and collaboration, thereby gaining a competitive advantage in the lifting equipment industry which ultimately contributes greatly to the growth of the company. For the knowledge management system implementation process, it will be divided into 4 (four) stages: Pre-Adaptation, Adaptation, Implementation, and Evaluation to ensure that the knowledge management system is implemented effectively, its impact can be measured, and areas for improvement can be identified to make necessary changes. Implementation will begin on the second half of 2023, to be specific in August 2023, and there will be a dedicated Person In Charge (PIC) for all knowledge management initiatives to monitor the progress and ensure the sustainability of this system.